"For whom was the Constitution made?": State, religion and politics in the constituent conventions of Córdoba (1923 and 1949) (Quinto Sol, 2022)
The present work goes through the constitutional texts in force in the province of Córdoba during three quarters of the 20th century, in which we see an intersection point between the legal and the political. We understand that the Constituent Conventions that shaped them provide us with a photograph of the very diverse moments of provincial political life in which they were sanctioned and that the debates that went through them open access doors to reconstruct the heterogeneous views about the relations between State, religion and society. This development allows us to identify transformations and permanence in their legal translation and in the different arguments that gave them sustenance.
Keywords: constitutional reform; discussions; religion; laicism